Components of an explanation for co-constructive sXAI - Vollmer, Anna-Lisa; Buhl, Heike M.; Alami, Rachid; Främling, Kary; Grimminger, Angela; Booshehri, Meisam; Ngonga Ngomo, Axel-Cyrille (Social Explainable AI)

Models of the situation, the explanandum, and the interaction partner - Buhl, Heike M.; Vollmer, Anna-Lisa; Alami, Rachid; Booshehri, Meisam; Främling, Kary (Social explainable AI)

Adaptation - Buhl, Heike M.; Wrede, Britta; Fisher, Josephine Beryl; Matarese, Marco (Social Explainable AI)

Practical considerations for assignment of photon numbers with SNSPDs - Schapeler, Timon; Mischke, Isabell; Schlue, Fabian; Stefszky, Michael; Brecht, Benjamin; Silberhorn, Christine; Bartley, Tim (APL Quantum)
Superconducting nanowire single-photon detectors (SNSPDs) can enable photon-number resolution (PNR) based on accurate measurements of the detector’s response time to few-photon optical pulses. In this work, we investigate the impact of the optical pulse shape and duration on the accuracy of this method. We find that Gaussian temporal pulse shapes yield cleaner arrival-time histograms and, thus, more accurate PNR, compared to bandpass-filtered pulses of equal bandwidth. For low system jitter and an optical pulse duration comparable to the other jitter contributions, photon numbers can be discriminated in our system with a commercial SNSPD. At 60 ps optical pulse duration, photon-number discrimination is significantly reduced. Furthermore, we highlight the importance of using the correct arrival-time histogram model when analyzing photon-number assignment. Using exponentially modified Gaussian distributions, instead of the commonly used Gaussian distributions, we can more accurately determine photon-number misidentification probabilities. Finally, we reconstruct the positive operator-valued measures of the detector, revealing sharp features that indicate the intrinsic PNR capabilities.

Defect Structure-Performance Correlation in Eu³⁺@UiO-66: Design of Coordination Sites for Rapid Optical O₂ Sensing - Zhao, Zhenyu; Tiemann, Michael (Journal of Materials Chemistry C)
Defect engineering offers an effective route to tailor the local coordination environment, gas transport and excited-state processes in metal-organic frameworks (MOFs). We establish a quantitative structure-property relationship linking defect-modulated porosity...

Selective Use of Yannakakis’ Algorithm for Consistent Performance Gains - Böhm, Daniela; Gottlob, Georg; Lanzinger, Matthias; Longo, Davide Mario; Okulmus, Cem; Pichler, Reinhard; Selzer, Alexander (Proceedings of the 28th International Workshop on Design, Optimization, Languages and Analytical Processing of Big Data (DOLAP 2026))
Large intermediate results can cause join queries to run unexpectedly long. This problem is particularly common for analytical queries, which aggregate data over many tables to produce a comparatively small final output, and queries on graph data, where intermediate results blow up quickly. Recent work inspired by Yannakakis’ algorithm approaches this by modifying the query engine to avoid materializing unnecessary tuples. However, this requires significant changes to the core of the system, which is not feasible in many situations such as cloud environments or proprietary systems. In this work, we propose a flexible approach for optimizing long-running join queries from the outside of the DBMS. Rewriting-based realizations of Yannakakis’ algorithm suffer from inherent overhead due to the creation of intermediate tables. Thus, we present an approach for detecting and targeting queries which would benefit from a Yannakakis-style optimization. We introduce a new benchmark combining 5 standard benchmarks and augmenting them with additional instances, which provides a sufficient size and diversity for a machine learning based solution. On PostgreSQL, DuckDB and SparkSQL, slowdowns on queries where the rewriting is counterproductive are mostly avoided, as opposed to a naïve application of the rewriting, and we observe significant improvements in end-to-end runtimes over standard query execution and unconditional rewriting.
Keywords: Join Queries; Acyclic Queries; Query Processing

Reason and Communication: Jürgen Habermas’s Legacy for Media and Communication Studies - Fuchs, Christian (tripleC: Communication, Capitalism & Critique)

Bridging the Dual Nature: How Integrated Explanations Enhance Understanding of Technical Artifacts - Terfloth, Lutz; Buhl, Heike M.; Lohmer, Vivien; Schaffer, Michael; Kern, Frederike; Schulte, Carsten

Decentring the governance of AI in the military: a focus on the postcolonial subject - Bhila, Ishmael (AI and Ethics)
The governance of emerging technologies with increased autonomy in the military has become a topical issue in recent years, especially considering the rapid advances in artificial intelligence and related innovations in computer science. Despite this hype, the postcolonial subject’s position has been seen as secondary, often associated with victimhood or obscurity. By shifting the narrative to highlight the postcolonial subject’s agency—not only in providing real-world examples of artificial intelligence use in the military but also in knowledge creation and shaping the discourse on governance within the international, this paper contributes to an area of research that is often overlooked. The paper unpacks the norm-making efforts of postcolonial subjects regarding emerging military technologies. In doing this, the paper aims to advance postcolonial theory by showing how the dynamics of governing emerging military technologies intertwine with postcolonial subjectivity and to broaden the academic discussion on the governance of emerging military technologies and algorithmic violence, which has so far been dominated by Western or universalistic discourse.

The Schrödinger equation with fractional Laplacian on hyperbolic spaces and homogeneous trees - Palmirotta, Guendalina; Sire, Yannick; Anker, Jean-Philippe (Journal of Differential Equations)
We investigate dispersive and Strichartz estimates for the Schrödinger equation involving the fractional Laplacian in real hyperbolic spaces and their discrete analogues, homogeneous trees. Due to the Knapp phenomenon, the Strichartz estimates on Euclidean spaces for the fractional Laplacian exhibit loss of derivatives. A similar phenomenon appears on real hyperbolic spaces. However, such a loss disappears on homogeneous trees, due to the triviality of the estimates for small times.
Keywords: Schrödinger equation; Fractional Laplacian; Dispersive estimates; Strichartz estimates; Real hyperbolic spaces; Homogeneous trees

Patterson-Sullivan distributions of finite regular graphs - Arends, Christian; Palmirotta, Guendalina (arXiv:2603.09779)
On finite regular graphs, we construct Patterson-Sullivan distributions associated with eigenfunctions of the discrete Laplace operator via their boundary values on the phase space. These distributions are closely related to Wigner distributions defined via a pseudo-differential calculus on graphs, which appear naturally in the study of quantum chaos. Using a pairing formula, we prove that Patterson-Sullivan distributions are also related to invariant Ruelle distributions arising from the transfer operator of the geodesic flow on the shift space. Both relationships provide discrete analogues of results for compact hyperbolic surfaces obtained by Anantharaman-Zelditch and by Guillarmou-Hilgert-Weich.

Digital Fascism and Digital Capitalism - Fuchs, Christian (Philosophy & Social Criticism)

Symbolic haunting: first-generation university students’ limited sense of entitlement - Lin-Januszewski, Liang-Wen (British Journal of Sociology of Education)

Keuchen, Marion/ Lindemeyer, Sabine: Demokratiebildung anhand eines (schul-)seelsorglichen Rituals im Rahmen der Lehramtsausbildung - Keuchen, Marion; Lindemeyer, Sabine (Seelsorge im Lebensraum Schule. Ökumenische Perspektiven)

Influence of deposition temperature and thickness of ALD-TiO2 on planar perovskite solar cell performance - Qudsia, Syeda; Weiss, Alexander; Sirkiä, Saara; Wang, Fuzeng; Rosqvist, Emil; Los Arcos, Teresa De; Weinberger, Christian; Halme, Janne; Kemell, Marianna; Smått, Jan-Henrik (Applied Surface Science)
In perovskite solar cells (PSCs), electron transport layers (ETLs) play an important role in the selection and transport of electrons. Understanding the properties of these layers in relation to device performance is essential for optimizing solar cell efficiency and enabling their integration into emerging architectures, such as flexible solar cells. Here, we deposited TiO2 at different thicknesses using atomic layer deposition (ALD), a technique well-suited for producing uniform and pinhole-free films. The crystal structure of the layers was controlled by depositing the films at three different temperatures: 150 °C, 250 °C, and 350 °C. The layers were characterized in detail to determine the morphology (by atomic force microscopy), surface composition (by X-ray photoelectron spectroscopy) and the crystal structure (by X-ray diffraction). The TiO2 layers were then incorporated as ETLs in planar perovskite solar cells to evaluate their influence on device performance. Higher deposition temperatures led to improvements in device fill factor and open-circuit voltage, leading to more efficient solar cells. Notably, the best device performance for the ALD-TiO2 layers was achieved with films deposited at 250 °C.
Keywords: Titanium dioxide; Atomic layer deposition; Electron transport layer; Perovskite solar cells

Vom „Push the Keys“ zum „Touch the Screen“? Eine Spurensuche zur Konkurrenz der Dinge im Musikunterricht. - Godau, Marc (Beiträge empirischer Musikpädagogik)
Der Beitrag untersucht die Einführung von iPads im Musikunterricht einer Sekundarschule aus einer soziomaterialen Perspektive. Auf der Grundlage einer mehrjährigen Begleitung wird mit Verfahren der Situationsanalyse aufgezeigt, wie die Digitaltechnologien – insbesondere die App GarageBand – in bestehende Fachkulturen, Dingordnungen und Unterrichtsroutinen eingebettet werden. Die Analyse offenbart, wie im Musikunterricht der Digitalisierungsprozess oft an alten Dingen, vertrauten Routinen und fachimmanenten Ideologien, wie dem Klaviozentrismus und einer Liveness-Norm, scheitert. Zugleich ergänzt ein alternatives Verständnis unterrichtlichen Musiklernens das handwerkliche Reproduzieren und Selbstüberwinden in Präsenzdarbietungen um die Klangarbeit beim explorativ-selbstständigen Erfinden und Produzieren präziser Aufnahmen. Die Ergebnisse werden hinsichtlich der Debatten um Digitalisierung in Schule und Musikunterricht diskutiert.
Keywords: Digitalisierung; GarageBand; Tablet-Klassen; Fachkultur; Situationsanalyse

Institutionalisierung der schulpraktischen Ausbildung im Ausland: Empirische Befunde zu Entwicklungen und Möglichkeiten neuer Wege in der Lehrer*innenbildung - Spiekenheuer, Mara; Freitag, Christine; Koch, Lea (PraxisForschungLehrer*innenBildung. Zeitschrift für Schul- Und Professionsentwicklung.)

Chancen und Herausforderungen des Krisenbegriffs zur Untersuchung historischen Lernens im bilingualen Geschichtsunterricht. Werkstattbericht eines Dissertationsprojekts - Pilz, Franziska (Geschichtslernen in Zeiten der Krise)

Evi:P - Evaluationsinstrument für eine partizipative und inklusive Praxis in der Kindertagesbetreuung - Albers, Timm; Meusel, Sarah

Vollständige Bestimmung der akustischen Materialparameter von Polymeren II - Dreiling, Dmitrij; Itner, Dominik; Birk, Carolin; Gravenkamp, Hauke; Henning, Bernd
In diesem Forschungsprojekt wurde ein Messverfahren zur Bestimmung akustischer Materialparameter von Polymeren im Ultraschallfrequenzbereich entwickelt. Das Verfahrens sollte, die üblichen standardisierten Prüfmethoden erweitern, die bislang primär im quasistatischen oder niederfrequenten Bereich eingesetzt wurden. Im Gegensatz zu bestehenden Verfahren wie dem Zeitstandversuch oder der Dynamisch Mechanischen Analyse (DMA) nach [DIN6721] sollte die neue Methode eine nicht-invasive Charakterisierung der (visko-)elastischen Materialparameter im Frequenzbereich von 0,75 MHz bis 2,5 MHz ermöglichen. Das entwickelte Ultraschallmesssystem arbeitet nach dem Puls Echo-Prinzip und kann eine räumlich segmentierte, ringförmige Anregung erzeugen. Die Bestimmung der frequenzabhängigen Materialparameter geschieht hierbei über ein inverses Verfahren. Die Ergebnisse des Projekts zeigen, dass die Segmentierung der Anregung, die Geometrie der Probe sowie das Puls-Echo-Messprinzip die Messergebnisse sowie die Sensitivität gegenüber Scherparametern wesentlich beeinflussen. Im Rahmen des Projektes wurde auch eine statistische Auswertung des Optimierungsverfahrens hinsichtlich transversal-isotroper Materialsymmetrie mit Rayleigh-Dämpfung durchgeführt. Die Ergebnisse zeigen, dass das entwickelte Verfahren gute Konvergenzeigenschaften aufweist und sich durch verbesserte Robustheit auszeichnet.
Keywords: Materialcharakterisierung; Polymer; Inverses Problem; Ultraschall; Optimierung